Pongamia as a potential biofuel crop: Oil content of Pongamia pinnata from the best provenance in Java, Indonesia - Hasnah, T.; Leksono, B.; Sumedi, N.; Windyarini, E.; Adinugraha, H.A.; Baral, H.; Artati, Y. (Institute of Electrical and Electronics Engineers, 2020)
Pongamia pinnata (L.) Pierre is a fast-growing, leguminous and multipurpose tree species. It grows on degraded and marginal land in South and Southeast Asia. It produces nonedible seeds the oil of which is a potential biofuel. In Indonesia, Pongamia is widely found on all islands but mostly to the west of the Wallace line, such as Banten, East Java, South Sumatra, and West Java provinces. The economic feasibility of Pongamia depends on the number of seed per tree and the oil content of the seed. Studies on Pongamia oil in Indonesia revealed that trees grown in Ujung Kulon National Park, Banten Province, produce seed with a higher oil content (i.e., 15.59 % ) than those in the provinces of East and West Java using simple mechanical expeller press. In this study the oil content of 48 individual trees, from Ujung Kulon National Park, were analyzed using a solvent extraction method. As a control, bulk seed was extracted using two different methods: 1) fabricant mechanical screw expeller press and 2) solvent extraction. The results show highly significant or great variation in the oil content of the trees. Oil production of individual trees processed using the solvent extraction method reached 44% (varies from 26.61% to 44.68 % ) than those by mechanical pressing method with bulk seed was only 15 to 19%. The findings show that genetic factors, extraction machines and the method of extraction could all influence the production of Pongamia oil. The quality and genetic diversity of seed source is also very important on industrial plantation forest program for bioenergy and land restoration in Indonesia.